2016
DOI: 10.1111/fcre.12224
|View full text |Cite
|
Sign up to set email alerts
|

Relocation Issues in Child Custody Evaluations: A Survey of Professionals

Abstract: We report on a sample of 90 child custody evaluators in the United States, who completed an online questionnaire on their attitudes and beliefs in child custody relocation cases. Findings indicated that the vast majority of participants relied on relevant professional literature and utilized a relocation risk assessment forensic model. Participants found many risk, protective, and specific relocation factors important, but the triad of past parental involvement, support for the other parent, and child's age we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
(42 reference statements)
0
4
0
6
Order By: Relevance
“…These conceptual and research articles from scholars in Australia, England, and New Zealand provide breadth and creativity for our understanding of these perplexing custody disputes known as “relocation cases.” This qualitative research contrasts with, but is complementary to, the large quantitative research literature on the effects of residential mobility on children of divorce and how a myriad of factors affect children's adjustment to divorce, as discussed below. Both literatures are also summarized in Parkinson, Taylor, Cashmore, and Austin ().…”
Section: Parkinson and Cashmore's Qualitative Research On Relocationmentioning
confidence: 99%
See 1 more Smart Citation
“…These conceptual and research articles from scholars in Australia, England, and New Zealand provide breadth and creativity for our understanding of these perplexing custody disputes known as “relocation cases.” This qualitative research contrasts with, but is complementary to, the large quantitative research literature on the effects of residential mobility on children of divorce and how a myriad of factors affect children's adjustment to divorce, as discussed below. Both literatures are also summarized in Parkinson, Taylor, Cashmore, and Austin ().…”
Section: Parkinson and Cashmore's Qualitative Research On Relocationmentioning
confidence: 99%
“…The risk assessment model can be a part of the evaluator's systematic approach. A recent survey found that about two‐thirds of evaluators indicate they use the model (Austin, Bow, Knoll, & Ellens, ). The research‐based factors in the model overlap with and resemble commonly found relocation legal factors (e.g., LaMusga ).…”
Section: Factorial Analysis In Relocation Disputesmentioning
confidence: 99%
“…No obstante, en los datos ofrecidos por el INE (2018) constan los casos de divorcio en los que uno o ambos conyugues eran extranjeros (en el 10.9% de los casos de divorcio uno de los cónyuges era extranjero y en el 6.3% ambos cónyuges eran extranjeros), situación que según refieren algunos autores (Rodríguez-Domínguez, Jarne y Carbonell, 2015) ha hecho incrementar el número de traslados internacionales. Asimismo, algunos estudios (Austin, Bow, Knoll y Ellens, 2016;Austin y Rappaport, 2018;Kelly Anuario de Psicología Jurídica (2019) y Lamb, 2003;Strous, 2007;Warshak, 2013) señalan que en general los progenitores divorciados presentan una tasa elevada de movilidad residencial, siendo los progenitores con hijos de corta edad los que presentan las tasas más altas. Además, se aprecia que son mayoritariamente las madres quienes desean trasladarse y, consecuentemente, quienes suelen instar los procedimientos judiciales solicitando autorización para ello (Taylor, Gollop y Henaghan, 2010).…”
unclassified
“…Si bien en procesos de separación o divorcio contenciosos la valoración del sistema de tenencia más adecuado a las necesidades de los hijos menores supone un reto para los profesionales (American Psychological Association, 2010;Austin et al, 2016;Pickar, 2007), los casos de traslado aún conllevan mayor complejidad (Atkinson, 2010;Austin, 2000a;Burt, 2011;Kelly y Lamb, 2003;Saini, Allan-Ebron y Barnes, 2015;Stahl, 2013;Strous, 2007;Waldron, 2005). La dificultad radica en la dicotomía a evaluar (traslado vs. no traslado), no existiendo un término medio en la decisión a adoptar.…”
unclassified
See 1 more Smart Citation